Communications Trend Radar 2024. Information inflation, AI literacy, workforce shift, content integrity & decoding humans - Stefan Stieglitz; Ansgar Zerfaß; Michelle Wloka; Sünje Clausen (Academic Society for Management & Communication, 2024)
What does the future hold for corporate communications? The Communications Trend Radar is an applied research project. On an annual basis, it identifies relevant trends for corporate communications from the fields of society, management, and technology. The research team at the University of Potsdam (Professor Stefan Stieglitz, Sünje Clausen, MS.) and Leipzig University (Professor Ansgar Zerfass, Dr Michelle Wloka) identified the following trends for 2024: Information Inflation, AI Literacy, Workforce Shift, Content Integrity, Decoding Humans. More information on the trends can be found in the Communications Trend Radar Report 2024 – – Wo steht die Kommunikationsbranche und wohin wird sie sich entwickeln? Der Communications Trend Radar ist eine wissenschaftliche, interessensunabhängige Studie, die jedes Jahr relevante Trends für die Unternehmenskommunikation aus den Bereichen Gesellschaft, Management und Technologie herausarbeitet. Das Forschungsteam der Universität Potsdam (Prof. Dr. Stefan Stieglitz, Sünje Clausen, M.Sc.) und der Universität Leipzig (Prof. Dr. Ansgar Zerfaß, Dr. Michelle Wloka) identifiziert für 2024 die Trends: Information Inflation, AI Literacy, Workforce Shift, Content Integrity, Decoding Humans. Weitere Informationen zu den Trends können im Communications Trend Radar Report 2024 nachgelesen werden.
Keywords: 650